Bone Metabolism Alterations in Systemic Sclerosis: An Insight into Bone Disease in SSc: From the Radiographic Findings to their Potential Pathogenesis and Outcome - Sciacca, Stefania; Corrado, Addolorata; Rotondo, Cinzia; Cantatore, Francesco P. (Current Rheumatology Reviews, 2022)
Previous research has shown conflicting reports about the effect of systemic sclerosis (SSc) on bone metabolism, especially considering bone mineral density (BMD), bone microarchitecture, and risk of fracture. The objective of this review is to analyze data from previous articles to investigate the differences in BMD and fracture risk between SSc and non-SSc populations and to discuss potential underlying mechanisms. The main factors investigated have been BMD (mean and standard deviation), t-scores and z-scores at the lumbar spine, femoral neck, and total hip measured by dual-energy X-ray absorptiometry (DEXA), bone remodeling markers, fracture prevalence, and incidence, trabecular bone score (TBS), musculoskeletal involvement with particular correlation to SSc skin subtype and extent, disease duration, serological pattern, and vitamin D levels. Since microvascular alterations evaluated through nailfold videocapillaroscopy (NVC) of SSc patients have recently been correlated with decreased BMD and bone microarchitecture, the vascular impairment in SSc has been proposed as a remarkable contributing element in bone remodeling, and the role of hypoxia has been investigated.
Keywords: bone turnover markers